The Ottoman Status Quo Regime and the Christian Sects in Jerusalem in the Late Nineteenth Century - Al Tarawneh, Fatima Salim (Advances in Social Sciences Research Journal, 2019)
What is known as the Status Quo Law is actually a law promulgated by the Ottoman State which ruled Jerusalem and the Arab lands in the middle of the nineteenth century and beyond after prolonged years of disputes between the Christian sects and communities subject to the suzerainty of the Ottoman State in Jerusalem, not to mention the interventions of European states, each one of which attempted to secure privileges inside Jerusalem. Actually, France was the first European state to secure capitulations (privileges) from the Ottoman state, followed by a number of other Europeans states at a subsequent time, the first of which was Britain which obtained commercial capitulations in the year 1580 A.D., followed by the Netherlands in 1612 A.D., and then Austria in 1616 A.D., followed by other states a century later or more, such as Sweden, Sicily, Denmark, Prussia and Spain. The abovementioned states utilized those concessions to be protectors of one or another of the Orthodox or Catholic sects in Jerusalem, where France was the protector of the Latin Catholics, and Russia of the Orthodox. Thus disputes between the Christian sects intensified as a consequence, which led to the Turkish Sultans issuing a firman since the year 1740 A.D. known as the Status Quo to each Christian sect safeguarding their rights in the holy places which established the rights of every sect and religious community which was present in Jerusalem, without permitting undertaking any change to the status quo since that date until the status was firmly established in 1852, and thus the rights of the various religious sects and communities were protected, at the forefront of which were the rights of the Christian sects in the Church of the Holy Sepulcher. In reality the law is still to a great extent in effect till today.